The Effect Of Current Ratio, Debt To Equity Ratio, And Price To Book Value On Financial Performance Of Property And Real Estate Sector Companies Listed On The Indonesia Stock Exchange In 2021-2023 - Julianti, Eka; Rita Friyani; Eko Prasetyo (International Journal of Economic Research and Financial Accounting, 2025)
This study examines the influence of the Current Ratio, Debt to Equity Ratio, and Price to Book Value on the financial performance of property and real estate companies listed on the Indonesia Stock Exchange during the period 2021 to 2023. Financial performance is measured using Return on Assets (ROA), while the independent variables consist of Current Ratio (CR), Debt to Equity Ratio (DER), and Price to Book Value (PBV). The study employs a quantitative method with an explanatory approach and uses secondary data from 83 companies over three years, resulting in 249 firm-year observations. Multiple linear regression analysis was used to examine the relationships among variables, with the assistance of SPSS software. The results show that simultaneously, CR, DER, and PBV have a significant effect on financial performance. Partially, CR and PBV have a positive and significant effect, while DER has a negative and significant effect on ROA. These findings highlight the importance of liquidity, capital structure decisions, and market valuation in enhancing company profitability. This study contributes to financial decision-making practices for company management and investors in the property and real estate sector.